Trade Responses to COVID-19 Food Security Concerns in Bangladesh - Dihel, Nora (World Bank, Washington, DC, 2020)
The COVID-19 (coronavirus) health crisis can lead to a food security crisis in Bangladesh if proper measures are not put in place. Trade policies can be an essential instrument in the management of the COVID-19 (coronavirus) related food security issues. Trade responses such as eliminating tariffs, refraining from imposing export restrictions, and facilitating trade flows can play an important role in maintaining access to and reducing the cost of essential food products.